Single crystal hybrid perovskite field-effect transistors - Yu, Weili; Li, Feng; Yu, Liyang; Niazi, Muhammad R.; Zou, Yuting; Corzo, Daniel; Basu, Aniruddha; Ma, Chun; Dey, Sukumar; Tietze, Max L.; Buttner, Ulrich; Wang, Xianbin; et al. (Nature communications, 2018)
The fields of photovoltaics, photodetection and light emission have seen tremendous activity in recent years with the advent of hybrid organic-inorganic perovskites. Yet, there have been far fewer reports of perovskite-based field-effect transistors. The lateral and interfacial transport requirements of transistors make them particularly vulnerable to surface contamination and defects rife in polycrystalline films and bulk single crystals. Here, we demonstrate a spatially-confined inverse temperature crystallization strategy which synthesizes micrometre-thin single crystals of methylammonium lead halide perovskites MAPbX 3 (X = Cl, Br, I) with sub-nanometer surface roughness and very low surface contamination. These benefit the integration of MAPbX 3 crystals into ambipolar transistors and yield record, room-temperature field-effect mobility up to 4.7 and 1.5 cm 2 V −1 s −1 in p and n channel devices respectively, with 10 4 to 10 5 on-off ratio and low turn-on voltages. This work paves the way for integrating hybrid perovskite crystals into printed, flexible and transparent electronics. The methylammonium lead halide perovskites have shown excellent optoelectronic properties but the field-effect transistors are much less studied. Here Yu et al. synthesize micrometer-thin crystals of perovskites with low surface contamination and make ambipolar transistor devices with high mobilities.